2023
DOI: 10.1155/2023/3185746
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Alternated Inertial Projection and Contraction Algorithm for Solving Bilevel Variational Inequality Problems

Abstract: This paper considers an alternated inertial-type extrapolation algorithm for solving bilevel pseudomonotone variational inequality problem in the framework of real Hilbert spaces with split variational inequality and fixed-point constraints of demimetric mapping. The algorithm which involves alternated inertial uses self-adjustment stepsize condition that depends solely on the information from previous iterative step. The bilevel problem considered in the work consists of upper-level problem with an underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We denote by V(K, F) the solution set of the VIP (1). Problem (1) has a wide range of applications; several methods for solving this problem have been developed by many researchers (see [1][2][3] and the references in them).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We denote by V(K, F) the solution set of the VIP (1). Problem (1) has a wide range of applications; several methods for solving this problem have been developed by many researchers (see [1][2][3] and the references in them).…”
Section: Introductionmentioning
confidence: 99%
“…A common feature of the inertial-type algorithm is that the next iteration depends on the combination of two previous iterates; for more details, see [3,18,19]. Many inertial-type algorithms have been studied and numerical tests have demonstrated that the inertial effects on these methods greatly improve their performances; see [1,3,20]. Recently, Lorenz and Pock [17] introduced and studied the following inertial FBA to solve the MIP (2):…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations